(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2019)
The pollution caused by sodium dodecyl sulfate (SDS) arise mainly from its utilization as detergent in industrial washing, which results in the high effluent level of this contaminant. SDS as anionic surfactant is ubiquitously toxic to the aquatic ecosystem. In this study, the potentials of a previously isolated molybdenum-reducing Bacillus amyloliquefaciens strain KIK-12 to degrade and utilize SDS as sole source of carbon was investigated. The bacterium grew optimally at pH between 6.0 and 7.0, temperature between 30 and 45 Â°C in 1 g/L SDS as the sole source of carbon, with ammonium sulphate (1 % w/v) as the best nitrogen source. The growth characteristics of strain KIK-12 on various concentrations of SDS (as a carbon source) reveals optimum growth 500 mg/L but was able to tolerate and grow at 1500 mg/L. However, concentrations higher than this results in growth termination. Heavy metals such as mercury, silver and copper significantly inhibit growth of strain KIK-12 on SDS. The ability of this bacterium to tolerate and detoxify multiple toxicants makes it suitable for their bioremediation.